Integration of sustainability dimensions into the valuation of process industries in Nigeria / Abayomi Olusola Ibiyemi - Abayomi Olusola, Ibiyemi (2018)
The primary role of the valuer in response to the climate change-related issues would be to induce and adopt measures that can integrate sustainability adjustments into the valuation process. Real estate valuers, as stakeholders, could also play a contributory role to sustainable development by giving sustainability-driven advice to clients and reflecting sustainability capacities of process industries in property valuation based on investment value. Valuation theory and practice remain without a methodological approach for incorporating sustainability issues into process industries in Nigeria. Even now, it seems problematic to value process industries for sustainability on a basis other than market value, such as investment value, and for purposes such as individual investment and operational objectives. It denotes that a gap exists in the real estate valuation theory and practice. In the absence of an appropriate methodology, this study explores the Delphi method. The quantitative research method was employed. The study discusses the case for sustainability, emerging normative, and the evidence-based valuation approaches, sustainability indicators, green building tools and sustainability drivers, and the knowledge-based supports systems. It develops a valuation approach based on the modified cost method of valuation to specify the methodological advances for assessing the extent to which the sustainability features of the case study industry meet the specified sustainability criteria. The Delphi method sets twenty-three (23) experts into two heterogeneous panels. The experts identified 39 indicators and scored the indicators after individual industrial surveys, direct observation, and an examination of the environmental audit report on the case study industry. The GreenstarSA (2007) equal scoring weights of 10/2 was adopted for the determination of the scores by the experts. This study found sixteen (16) critical sustainability indicators (four from each of the four specified dimensions) for the paints' industry in Nigeria. It also obtained the Industrial Sustainability-Related Obsolescence Correction Factor (ISRO-CF) of 0.671 as the sustainability-based performance of the industry, and the fair value to the industry owner based on specific theoretical considerations such as externalities, impact compliance, expectation, substitution, and inducement. The data triangulation method was used to validate the study. The valuation approach builds knowledge for theory construction and evokes the design choices from the subjective-intuitive Delphi techniques of foresight through expert consensus opinion. For practical application purposes, it initiates the integration of the multidisciplinary dimension for valuing process industries which could be used as a template for estimating the industrial sustainability compliance for real estate valuation on the investment value basis. The prime expectations are that valuers can proceed with the valuation of process industries for sustainability, induce the keenness of industries to certify their buildings, while also making real estate valuation sustainability-compliant and responsible. Valuers’ knowledge-support and perceptive studies justify the acceptability and suitability of the valuation approach and elicit the significant predictors of the support system. The study claims that there is an impact perspective to industrial sustainability in real estate valuation. The ISRO-CF approach complies with the RICS Valuation Practice Statements VPS.4 [2.5g: 3-4] of 2014.